Analisis Perbandingan Kinerja Keuangan Pada Masa Pandemi Covid-19 Dan Era New Normal Perusahaan Sektor Transportasi Di Bursa Efek Indonesia - Muhamad Cikhal Anwar; Wastam Wahyu Hidayat; Eri Bukhari; Murti Wijayanti (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Indonesia Stock Exchange during the COVID-19 pandemic and the transition to the New Normal era. The pandemic significantly impacted this sector, particularly by reducing revenue and profitability. This study aims to compare the Current Ratio (CR), Return on Assets (ROA), Debt to Equity Ratio (DER), and Total Assets Turnover (TATO) between these two periods. A quantitative approach with a comparative analysis method was employed. The data were obtained from the financial statements of transportation sector companies for the 2019–2020 and 2022–2023 periods. Statistical analyses, including normality assessment, descriptive statistics, and hypothesis testing using the Paired Sample T-test and Wilcoxon Signed Rank Test, were performed. The results indicate that only ROA showed a significant difference (p < 0.05), with profitability increasing after the pandemic. In contrast, CR (p > 0.05), DER (p > 0.05), and TATO (p > 0.05) did not exhibit significant differences. These findings suggest that the transition to the New Normal era positively impacted profitability but had no significant effect on liquidity, capital structure, or asset efficiency. This study analyzes the financial performance of transportation sector companies listed on the